IMPROVING PERFORMANCE THROUGH JOB PROMOTION - Agus Naini Siregar; Kiki Farida Ferine; Muhammad Isa Indrawan; Sri Rahayu (Universitas Efarina, 2025)
This study aims to analyze the effect of competence and education on employee performance with job promotion as an intervening variable at PT PLN (Persero) UP3 Medan Utara. The research is motivated by the importance of improving employee performance, which is not only influenced by individual abilities but also by job promotion opportunities as a form of recognition and career development. The research method employed is a quantitative approach using a questionnaire for data collection. The number of respondents in this study was 69 employees, selected through purposive sampling. The data were analyzed using Partial Least Square (PLS-SEM) to examine both direct and indirect relationships among variables. The results indicate that: (1) competence has a positive and significant effect on employee performance, (2) competence has a positive and significant effect on job promotion, (3) education does not have a significant effect on employee performance, (4) education has a positive and significant effect on job promotion, (5) job promotion has a positive and significant effect on employee performance, (6) job promotion mediates the relationship between competence and employee performance, and (7) job promotion also mediates the relationship between education and employee performance. Therefore, it can be concluded that competence and education are important factors in supporting job promotion, while job promotion serves as a key variable in enhancing employee performance at PT PLN (Persero) UP3 Medan Utara.